DISEASE DURATION AND HLA-B27 POSITIVITY ALTER LONGTERM RETENTION RATE OF CERTOLIZUMAB PEGOL IN PATIENTS WITH PSORIATIC ARTHRITIS - Koca, S. S.; Pehlivan, Y.; Akar, S.; Senel, S.; Karadeniz, H.; Sosyal, O.; Onen, F. (Elsevier, 2021)
[Abstract Not Available]
Annual European Congress of Rheumatology (EULAR) -- JUN 02-05, 2021 -- ELECTR NETWORK